Recognoscering på den nordlige del af Oman halvøen. En foreløbig rapport - Cardi, Beatrice de (Kuml, 1969)
A preliminary report of field survey in the northern Trucial States A brief visit in 1965 by Professor P. V. Glob and Mr. T. G. Bibby to Ras al-Khaimah and Dibba suggested the need for further survey in the northern Trucial States. With the permission of His Highness Sheikh Saqr bin Muhammed al-Qasimi, and with the cooperation of His Highness Sheikh Muhammad bin Hamad al-Sharqi, it was possible for Mr. D. B. Doe, M.B.E., F.R.I.B.A., F.S.A., and I to spend four weeks during February, 1968, in their respective States of Ras al-Khaimah and Fujairah. A primary object of the survey was the location of prehistoric sites which it was hoped might yield incised and painted grey wares of the kind found on late third millennium sites in south-eastern Iran and in the burial cairns of Umm an-Nar and Hili, near Buraimi, in the Sheikhdom of Abu Dhabi [I]. The northern Sheikhdom of Ras al-Khaimah and the Batina coast on the east of the peninsula, from Kalba to Khawr Fakkan, seemed the obvious areas to explore since they lie within easy reach of Baluchistan. No recognisably prehistoric sites were, however, discovered apart from stone burials of various types, which can only be described as pre-Islamic. The absence of prehistoric remains in the areas accessible to us is perhaps explained by the physiography of this part of the Oman peninsula which falls roughly into four types of terrain: the coastal plain on the east; the central mountain ranges; stony outwash fans merging into a narrow strip of alluvial plain, and the sandhills which stretch westwards to the sea. The chances of finding early settlements amidst the dunes seemed singularly remote and our survey was consequently restricted to the alluvial plain and to the entrances of the major wadis. Reconnaissance showed that only structures such as cairns and buildings with solid foundations had survived on the well-scoured gravels at the mouth of the wadis. In the plains, the majority of sites discovered could be dated by the surface pottery to the period of the Portuguese occupation (16th-17th centuries) and it is likely that any prehistoric sites which may have existed now lie below alluvial deposits and will only be revealed by chance. The mountains to the north-east of Ras al-Khaimah lie in Muscat territory and were not accessible, while the xenophobia of the Shihuh prevented exploration in the foothills. Within the regions surveyed, about three dozen sites were found including ruined towns, hillforts and fortified houses, the latter belonging to the Portuguese period, caves, rockcarvings and cairns of various types. Ras al-Khaimah Our survey started in the northern zone of Ras al-Khaimah. Near Ash Sham (map, No. 1), which marks the start of Muscat territory to the north, a ruined settlement was found at the foot of the hills with six mosques, built at different periods to judge by their masonry. Although the settlement is said to have been in occupation for a long time, no pottery earlier than some 18th-century Chinese porcelain was identified. In the wadi behind this site rock-carvings representing horsemen were noted on a boulder near a stepped and paved track leading to an ancient hill-village. This settlement had been built at well over 500 ft. above the wadi bed, a feature of importance being a large water cistern set in a well-protected position against the rock face. From Ash Sham the caravan route runs southwards at the foot of the hills to the Wadi Ghalilah (No. 2). Here it was possible to save three out of a group of five found cairns from bulldozing. They consisted of roughly-dressed masonry with corbelled roofs covered by smaller stones and stood in some cases to a height of six feet. Graves of a different type occurred near the entrance to the Wadi Haqil (No. 3) further south. These were roughly oblong stone-built structures with apsidal ends, their length varying from 28 to 87 ft., but their width only ranging from 8 to 10 ft. Each grave had been covered by large stone slabs and stones set at right angles marked the single entrance placed midway along the perimeter wall. An attempt to excavate one of these graves aroused much opposition locally and had to be abandoned after the discovery of a small round-based buff ware pot beside some crushed bones. The Wadi Haqil was evidently an area of importance in antiquity and other remains included a large stone-built hillfort guarding the entrance to the valley. At its foot, a stone-faced dam had been built across the plain for about four miles to divert flood water towards the date groves near the old seaport of Julfar (No. 4). The ruins of Julfar stretch for over a mile along a sandspit north of the creek which separates it from the town of Ras al-Khaimah. Julfar is said locally to have been founded in Abbasid times and it probably owed its rise to the growth of trade in the Gulf during the period when Siraf was at the height of its prosperity. When Siraf declined, Kish became the chief entrepot until the rise of Hormuz in the early 14th century. Coastal Oman, if not the interior, had come under the control of the Kings of Hormuz in the previous century and their continued until the arrival of the Portuguese at the beginning of the 16th century. At the time, Julfar is described as a prosperous port yielding good revenues [2] and the recent survey suggests that it continued to serve as a distribution centre for the hinterland during the Portuguese occupation. Among the goods imported by its merchants was much Ming blue-on-white porcelain ascribed to the latter half of the 16th century [3], a period when this ware was being mass-produced by the Chinese. The Portuguese were exporting it in quantity from Macao to Goa, and from there it was widely distributed through India, along the Gulf and down the East African coast. Little attention has been paid to the coarser Chinese export wares until recently, with the result that adequately published comparative material from excavated sites is scarce. Nor is it easy at this stage to determine to what extent the Chinese factories were catering for different markets. Some differentiation is evident both in the quality and type of vessels exported; for instance, the vases and ewers destined for Iran are clearly in a higher price range than the humbler eating-bowls, cups and dishes which reached Oman and East Africa in the 16th century. In addition to Ming blue-on-white porcelain, Julfar yielded fragments of large brownglazed Martabani jars, Annamese stoneware, and imitation celadons made probably in south-east Asia, but not necessarily in China. Local wares included a distinctive handmade, cream-slipped pottery used often for bridge-spouted ablution jugs painted with vertical red stripes. Although this ware had a westerly zoning in Ras al-Khaimah it provides a useful link with more distant regions since comparable jugs occurred in the Islamic Palace levels at Qala’at al-Bahrain and in 15th-16th century contexts at Siraf and Kilwa [4]. This ware was also present in the debris collected from an eroded cliff-site, Kashm Nadir (No. 5), a few miles south of Ras al-Khaimah town. The assemblage was essentially utilitarian and included a number of hand-made cooking-pots with four sharply triangular lugs set on the shoulder, a form which has close parallels at Siraf, Site E. Small saucers in a hard fabric with a mottled brown glaze are also numerous and can be matched by 17th-century material from Gedi on the coast of East Africa [5]. Both at Kashm Nadir and elsewhere, Persian wares were notably scarce but they included a little 17th-century Kerman underglaze blue-on-white pottery. Some earlier wares were found on the slopes of a demolished fort at Khawran (No. 6), to the south-east of Ras al-Khaimah, one of the few sites with pre-Portuguese occupation. Sherds found there included some brown sgraffiato ware, a single example of Sasanian-Islamic ware. and fragmentary bowls painted in dark brown under a light bluish glaze. The Batina coast From Ras al-Khaimah we crossed the peninsula via Manamah, Masafi and down the Wadi Ham to the Batina coast. Sites in the region north of Kalba lay in the narrow strip between the sea and the mountains but they were difficult to date in the absence of recognisable wares. Ming porcelain and some celadon was found on a deserted site just north of Khawr Fakkan (No. 8) South of that port, groups of small circular cairns. built in cloverleaf complexes of up to three, were noted at Qurayyah (No. 9) and over a hundred studded a hillside behind Kalba (No. 10) in neither case was any pottery associated with these structures. Conclusions The settlement pattern emerging from the survey, particularly in Ras al-Khaimah, suggests that the foothills were occupied in preference to the plains during the earlier periods, with hillforts guarding the approaches to the major wadis. Some camps were probably of flimsy structures comparable to the present barastis, which might account for the conspicuous absence of occupation near concentrations of cairns. Few sites could be ascribed with certainty to the Islamic period, apart from Khawran, and the port of Julfar, where occupation covering a period of about a thousand years would repay examination. The distribution of late Ming porcelain on the coastal sites of Ras al-Khaimah and the fortlets overlooking the interior probably reflect those areas directly under Portuguese rule. When the Portuguese abandoned their hold on the coasts around the Indian Ocean in the 17th century, they also lost control of the sea, and merchant shipping, particularly off the coast of Oman, suffered much from piracy. This may explain the paucity of later Chinese export wares in a region which had previously provided a good market. Beatrice de Cardi